2005
DOI: 10.1163/156856305323383892
|View full text |Cite
|
Sign up to set email alerts
|

Study on an injection quantity sensor. I: Evaluation of the integration procedure

Abstract: For 'on board' diagnosis purposes of the injected fuel quantity, ceramic flow sensor chips with a diameter of 2.2 mm were integrated into finished Common Rail injection nozzles of the valve covered orifice (VCO) or mini-sac hole (MSH) class. The influence of this integration step on the hydraulic performance of the high-precision injector nozzles which led to an optimized process flow with a minimized disturbance of the fluidic properties was investigated. Electron-discharge machining and electron-beam welding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Therefore, it is concluded that the radial bending of the nozzle tip caused by the EBW process is amplified when integrating in addition to the injection quantity sensor. This result is confirmed with the measurements of the injected fuel quantity (Schmid and Seidel 2005b) as well as on the optical investigation on the formation of spray cones (see Figs. 7,10) showing in both cases a lower deviation from the original state when only a welding seam is applied.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Therefore, it is concluded that the radial bending of the nozzle tip caused by the EBW process is amplified when integrating in addition to the injection quantity sensor. This result is confirmed with the measurements of the injected fuel quantity (Schmid and Seidel 2005b) as well as on the optical investigation on the formation of spray cones (see Figs. 7,10) showing in both cases a lower deviation from the original state when only a welding seam is applied.…”
Section: Discussionsupporting
confidence: 85%
“…It is therefore reasonable to assume that at these welding conditions, the angular distortion dominates the deformation of the work piece in contrast to transverse and longitudinal shrinkage effects. In comparison with the strong dependence of the injected fuel volume V IAI determined with the injection amount indicator (IAI) on electron beam welding parameters (Schmid and Seidel 2005b), it is confirmed that the geometrical distortion induced by the welding seam leads to a radial bending of the nozzle tip in the direction of the sealed access hole. The six injection holes are uncovered nonuniformly when the needle is lifted due to the perturbed axial symmetry along the nozzle axis.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The sensor fabrication and the corresponding integration process into the nozzle are described in detail elsewhere [14][15][16]. Basically, the device consists of a metallic thin film element on a pressure-stable LTCC substrate with integrated electrical feed-throughs.…”
Section: Sensor Fabrication and System Integration Processmentioning
confidence: 99%